Brotherband : Scorpion Mountain - Book 5 - Flanagan, John (John Anthony) (New York, NY : Philomel Books, an imprint of Penguin Group (USA), 2014)
Princess Cassandra of Araluen has already survived one assassination attempt, but when a second attempt proves that the deadly Scorpion Cult is involved, Hal, his Heron Brotherband crew, and the Ranger Gilan are dispatched to ensure her safety by launching a preemptive strike against Scorpion Mountain and its cult of assassins.
Keywords: Quests (Expeditions) -- Juvenile fiction; Seafaring life -- Juvenile fiction; Assassins -- Juvenile fiction; Attempted assassination -- Juvenile fiction; Adventure stories; Adventure and adventurers -- Fiction; Seafaring life -- Fiction; Assassins -- Fiction; Fantasy